DEVELOPMENT OF HISTORY FLASHCARD MEDIA ON THE MATERIAL OF THE ROLE OF ISLAMIC KINGDOM IN INDONESIA BASED ON SURAH AL-FATH VERSE 29 AT MTS AL WASHLIYAH 16 PERBAUNGAN - Dea Safitri; Eka Yusnaldi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
In order to teach the role of Islamic kingdoms in Indonesia at MTs Al Washliyah 16 Perbaungan, this project intends to create history flashcards based on Surah Al-Fath verse 29. Based on the ADDIE model which comprises the phases of Analysis, Design, Development, Implementation, and Evaluation the study used a Research and Development (R&D) methodology. Thirty eighth-grade students, one material expert, and one media expert were the research subjects. Questionnaires, observations, interviews, and learning outcome assessments were used to gather data, and a range of techniques were applied to examine the findings. Upon getting a 92% feasibility score from material experts and a 93% score from media experts, the generated media was considered extraordinarily viable based on the validation results. The percentage of pupils that actively participated rose from 35% to 83%, based on the implementation statistics. Learning outcomes also improved, with an average score that increased from 68.5 to 84.2 and a gain score of 0.50, which is in the moderate range. Both teachers and students praised the medium for its usefulness, appeal, and clarity. Incorporating Quranic themes into historical courses increased students' understanding of Islamic concepts. Thus, the produced History Flashcards media is valid, practical, and effective as a stand-in teaching tool for Islamic history at the Madrasah Tsanawiyah level.